Avoidant coping as mediator of the relationship between rumination and mental health among family caregivers of Chinese breast cancer patients. (17th October 2021) - Tan, Xing; An, Yuanyuan; Chen, Chen
Abstract: Introduction: Family caregivers of cancer patients were often referred to the 'forgotten patients', yet little researches have been conducted on their mental health. Rumination might put family caregivers at risk for psychological distress during the caregiving, such as stress and anxiety. The aim of the present study was to explore the relationship between rumination, stress and anxiety among family caregivers of breast cancer patients in China and examine the mediating role of avoidant coping in this relationship. Methods: Face‐to‐face questionnaire interviews were conducted with a sample of 99 caregivers from the public oncology hospital. They were assessed with stress, anxiety, rumination and avoidant coping by Chinese Perceived Stress Scale, Zung's Self‐Rating Anxiety Scale, Ruminative Responses Scale and Coping Strategy Indicator. Structural equation modelling was applied to assess the mediation analysis. Results: The reporting scores of participants indicated the incidence of anxiety was 17.2%. Rumination could directly predict stress ( β  = 0.58, p  < 0.01) and anxiety ( β  = 0.46, p  < 0.01) and also predict stress and anxiety via the mediator of avoidant coping (stress: β  = 0.087, p  < 0.01; anxiety: β  = 0.109, p  < 0.01). Conclusions: The important role played by family caregivers in supporting breast cancer patients is well recognised. The findings suggested that rumination and avoidant coping may be two critical risk factors for family caregivers of breast cancer developing stress and anxiety. This study highlights the importance of preventing avoidant coping, which plays a critical role for developing interventions for this vulnerable group.